Modifikasi Suhu Uji Pemunculan Radikula untuk Mempersingkat Pengujian Vigor Benih Jagung - Ul Khusna, Aghniya; Zamzami, Ahmad; Ilyas, Satriyas (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2021)
Radicle emergence (RE) is a rapid vigor test recommended by ISTA in 2014 for corn seeds at 20 oC for 66 hours. The purpose of this study was to develop an RE test of corn seeds at 25 °C and determine a single observation time to shorten the period of the vigor test. The experiments were conducted at IPB from December 2019 to March 2020. The experimental design used in the RE test was split-plot, with nine seed lots (cultivars) as main plots and 14 observation times (27, 30, 33, 36, 39, 42, 45, 48, 51, 54, 57, 60, 63, and 66 hours after sowing) as subplots. The completely randomized block design with one factor (seed lots) was used in the laboratory and field experiments. The result of the RE test was then correlated with seed and seedling quality parameters. The experimental results revealed that the RE test on corn seeds using between paper germinating method at 25 °C and observed at 51 hours ± 15 minutes after sowing, was closely correlated and could predict the normal germination percentage, mean germination time, vigor index, speed of germination, and mean emergence time. Keywords: correlation, cultivar, normal germination percentage, seed lot, seed vigor, seedling vigor